Single-port robotic transcervical long-segment thoracic tracheal reconstruction: Cadaveric proof-of-concept studyCentral MessagePerspective - Natalie S. Lui, MD, MAS, FACS; F. Christopher Holsinger, MD, FACS; Michael R. Ma, MD; Jeffrey R. Janus, MD; Karthik Balakrishnan, MD, MPH, FAAP, FACS (JTCVS Techniques)
Objective: Slide tracheoplasty is the standard technique to repair congenital long-segment tracheal stenosis. This operation most commonly requires median sternotomy, which has drawbacks in young children. We hypothesized that a transcervical approach without sternotomy would be feasible if done with a single-port robotic system. Methods: This proof-of concept study was performed in 2 small adult cadavers using a single-port robotic surgical system via a small neck incision. Relevant information, including operative time and details of operative technique, were recorded. Results: Long-segment slide tracheoplasty was completed successfully in 2 cadavers using a small neck incision and a single-port robotic surgical system. Strengths and pitfalls of the technique were identified, including technical refinements from the first attempt to the second. Operative time for robotic mobilization, incision, and anastomosis of the trachea was comparable to standard open approaches. Conclusions: Small-incision transcervical slide tracheoplasty, assisted by a single-port surgical robotic system, is feasible in a human cadaver. More work is needed to determine safety and applicability in live patients, particularly in children.